KEGIATAN PENILAIAN PEMBELAJARAN SENI BUDAYA MENGGUNAKAN APLIKASI PLICKERS DI SMAN 13 BANDAR LAMPUNG - Prameswari, Kurnia Widya; Setiawan, Afrizal Yudha; Saputri, Amelia Hani (Jurnal Seni dan Pembelajaran, 2023)
This research aims to describe how Arts and Culture Learning Assessment Activities Use the Plickers Application at SMAN 13 Bandar Lampung. There are six stages in carrying out assessment activities, namely determining objectives, determining assessment plans, preparing assessment instruments, collecting data or information, analysis and interpretation, and follow-up. The method used in this research is qualitative with data collection techniques, namely observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the arts and culture learning assessment activity using the Plickers application includes six stages, namely: (1) Selecting the type of formative assessment, (2) Selecting the form of assessment, accessing the account, creating a name, printing a card, (3) Creating 10 questions and inputting them into plickers application, (4) Start carrying out assessments using the plickers application, (5) Analyze and download answer results and question percentages on the plickers application, (6) Make decisions from student assessment results. As a whole, arts and culture learning assessment activities using the Plickers application have been carried out according to the stages by the teacher and received a positive response from students.